Hubungan aktivitas fisik dengan status gizi Siswa SMKN-03 Kabupaten Muko-Muko pada masa pandemi Covid-19 - Thesa Dwi Markuri; Salmi Salmi; Haves Ashan (ARGIPA (Arsip Gizi dan Pangan), 2021)
Overweight and obesity prevalence in Indonesian adolescents tend to increase in the last few decades. The decrease in physical activity is one of the risk factors for this case. Covid-19 pandemic has caused a physical activity decrease in adolescents. This study aimed to determine the relationship between physical activity and nutritional status among the SMKN 03 Muko-Muko students during covid-19 pandemic. This was analytic observational with a cross-sectional study. The study was followed by 76 of 12th grade SMKN 03 Muko-Muko district students that qualified for inclusion and exclusion criteria by purposive sampling. The physical activity level of the subject was determined by Global Physical Activity Questionnaire (GPAQ) and the nutritional status was determined using body mass index (BMI) and categorized based on the Asian-Pacific category. As the result, 69,7% of the subjects had a moderate level of physical activity and 30,3% in high level, respectively. As much as 48,6% of the subjects had normal BMI, 36,8% were underweight and 14,5% were overweight and obese. Statistical analysis by Chi-square concluded that there was a relationship between physical activity and nutritional status among the SMKN-03 Muko-Muko District students during covid-19 pandemic.